Perwujudan Demokrasi Ekonomi Melalui Hyperlocal Tokopedia - Ningsih, Sabda (Parahyangan Center for International Studies, 2023)
The Covid-19 pandemic has become a concern for all governments globally because it can affect the economy. In Indonesia, one of the government's focuses is how to solve problems related to MSMEs facing the threat of bankruptcy and the government's choice is to cooperate with e-commerce through hyperlocal. Hyperlocal for some researchers has the effect of changing the structure of cooperation and the logic of business organizations. However, the author himself argues that hyperlocal issues also have a role in identity transformation. This is based on the findings of several previous studies, that hyperlocal communication media influences the distribution of culture and the identity of certain community groups. By using the analytical framework of post-Fordism and constructivism, the author finds that Hyperlocal Tokopedia have influenced the identity of MSMEs in understanding